2020
DOI: 10.1108/pr-03-2020-0129
|View full text |Cite
|
Sign up to set email alerts
|

Supervisor bottom-line mentality and subordinates' unethical pro-organizational behavior

Abstract: PurposeThe multitude of high-profile corporate scandals has prompted the need for more nuanced understanding of factors within organizations that may influence unethical pro-organizational behavior (UPB). Based on the social cognitive theory, this study aims to examine the impact of supervisor bottom-line mentality (BLM) on unethical, but pro-organizational conduct by employees through moral disengagement. Additionally, this study examines the moderating role of employee mindfulness in relation of supervisor B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 109 publications
0
36
0
Order By: Relevance
“… 23 , 46 In contrast, supervisors with high level of BLM are typically focused on economic goals at the expense of employees, which makes subordinates appraise supervisor BLM as a hindrance stressor and in-turn reduce subordinates’ work performance. 2 , 4 Therefore, from the perspective of stress and coping, our study complements the literature of BLM by examining the double-edged sword effect of supervisor BLM on subordinates performance in a unified model, which provides useful empirical data to help analyze and understand the two sides of supervisor BLM.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“… 23 , 46 In contrast, supervisors with high level of BLM are typically focused on economic goals at the expense of employees, which makes subordinates appraise supervisor BLM as a hindrance stressor and in-turn reduce subordinates’ work performance. 2 , 4 Therefore, from the perspective of stress and coping, our study complements the literature of BLM by examining the double-edged sword effect of supervisor BLM on subordinates performance in a unified model, which provides useful empirical data to help analyze and understand the two sides of supervisor BLM.…”
Section: Discussionmentioning
confidence: 91%
“…In the past ten years, more and more research has focused on the positive or negative effects of supervisor bottom-line mentality in the workplace. 1 , 2 Bottom-line mentality (BLM) is defined as “a one-dimensional frame of thinking that revolves around securing bottom-line outcomes to the neglect of competing priorities”. 3 Supervisors who adopt BLM may consider that the bottom-line results, such as the achievement of financial goals, are the most important.…”
Section: Introductionmentioning
confidence: 99%
“…Our study also contributes to the management research that focuses on the drawbacks of BLM. Although a large majority of BLM research focuses on lower level employee drawbacks (e.g., Babalola et al, 2022; Eissa et al, 2019; Farasat & Azam, 2020; Farasat et al, 2020; Greenbaum et al, 2012; Quade et al, 2020; Zhang et al, 2020), some management scholars have focused on leadership drawbacks (Greenbaum et al, 2021; Rice & Reed, 2021). Whereas this stream of research has demonstrated that leader BLM adversely impacts leader sympathy (Greenbaum et al, 2021) and reduces engagement of goal-focused leadership (Rice & Reed, 2021), our study demonstrates leader BLM decreases ethical leadership and increases abusive supervision.…”
Section: Discussionmentioning
confidence: 99%
“…As this stream of research has noted that “BLM represents a dysfunctional and problematic mentality” (Rice & Reed, 2021, p. 3), management scholars have documented the various employee-level drawbacks associated with BLM (Mesdaghinia et al, 2019). Specifically, these employee-level drawbacks include increased inappropriate and undesirable employee behavior (Babalola et al, 2020; Eissa et al, 2019; Farasat & Azam, 2020; Farasat et al, 2020; Greenbaum et al, 2012; Quade et al, 2020; Zhang et al, 2020), increased customer-directed unethical behavior (Babalola et al, 2020), and decreased workgroup creativity (Greenbaum et al, 2020).…”
mentioning
confidence: 99%
“…Moreover, findings from extant literature indicate that BLM has a significant positive association with employee cheating behavior ( Farasat et al, 2020 ), abusive supervision ( Mawritz et al, 2017 ), subordinates’ knowledge hiding ( Li and Cheng, 2022 ), unethical pro-organizational behavior (UPB; Babalola et al, 2020b ; Farasat and Azam, 2020 ; Zhang et al, 2021 ), and unethical pro-leader behavior (ULB; Mesdaghinia et al, 2019 ). Hence, it is evident that BLM may temporarily enhance the financial health of the organization but that comes with a huge long-term cost, mainly in terms of undesirable and unethical employee conduct.…”
Section: Introductionmentioning
confidence: 99%